Chemokine CXCL1 as a potential marker of disease activity in systemic lupus erythematosus - Yanli Zeng; Qiaoduan Lin; Liang Yu; Xuelian Wang; Yiqiang Lin; Yan Zhang; Shuidi Yan; Xinxin Lu; Yijing Li; Weibin Li; Yun Xiao (BMC Immunology, 2021)
Abstract Objectives The chemokine CXCL1, known as growth-related oncogene α (GRO-α), is a potent chemoattractant and regulator of neutrophils. The purpose of our study was to evaluate the regulatory response of CXCL1 in the serum of patients with systemic lupus erythematosus (SLE) in the active stage of disease and to assess whether it was implicated in the pathogenesis/inflammatory process in lupus. Methods CXCL1 serum concentrations were examined in 90 SLE patients, 56 other autoimmune diseases (OADs) patients and 100 healthy controls using enzyme-linked immunosorbent methodology. Results SLE patients exhibited significant increases in serum CXCL1 concentrations [1492.86 (735.47–2887.34) pg/ml] compared with OADs patients [155.88 (10.77–366.78) pg/ml] and healthy controls [13.58 (8.46–37.22) pg/ml] (p < 0.001). Moreover, the level of CXCL1 decreased as the level of anti-dsDNA IgG decreased after treatment between the anti-dsDNA-positive SLE patients and the anti-dsDNA-negative SLE patients. Additionly, serum CXCL1 concentrations were related to different disease activity levels in SLE and lupus nephritis (LN) and high avidity of IgG ANAs (HA IgG ANAs) (p < 0.05). Furthermore, CXCL1 serum concentrations were significantly correlated with the SLE Disease Activity Index(SLEDAI) score, relative avidity index (RAI) of HA IgG ANAs and the levels of anti-dsDNA IgG, CRP, ESR, albumin, C3 and C4.Additionally, Statistical analysis revealed that positivity for IgG ANA (p < 0.001), the presence of HA IgG ANAs (p = 0.001) and the logarithmic level of anti-dsDNA IgG (p = 0.021) were significantly associated with the logarithmic level of CXCL1 with standard partial regression coefficients (95% CI) of 2.371 (1.734–3.009), 1.231 (0.52–1.937) and 0.409 (0.062–0.755), respectively. Finally, using cutoff points of 1182.17 pg/mL and 1500.31 pg/mL, serum CXCL1 levels had a similar sensitivity of 76% and specificity of 100% and 75% for the diagnosis of active SLE and LN, respectively. Conclusions Serum CXCL13 concentrations might represent a potential marker of disease activity in systemic lupus erythematosus.